Nuclear factor of activated T cells and early growth response-1 cooperate to mediate tissue factor gene induction by vascular endothelial growth factor in endothelial cells - Schabbauer, Gernot; Schweighofer, Bernhard; Mechtcheriakova, Diana; Lucerna, Markus; Binder, Bernd R.; Hofer, Erhard (Thrombosis and Haemostasis, 2007)
Based on the finding that tissue factor belongs to a group of genes upregulated in endothelial cells by VEGF, but not by EGF, we investigated signals selectively triggered by VEGF. Whereas the transcription factor early growth response (EGR)-1, which has previously been shown by us to be essentially involved in tissue factor gene regulation, was similarly induced by both factors, one major difference between VEGF and EGF signaling was the activation of the Ca++-mediated calcineurin/nuclear factor of activated T cells (NFAT) pathway by VEGF. Consistent with the importance of this pathway for tissue factor induction, treatment of endothelial cells with the Ca++ chelator BAPTA-AM, as well as the calcineurin inhibitor cyclosporin A, partially inhibited VEGF induced tissue factor upregulation. Furthermore, tissue factor reporter gene assays revealed a synergistic cooperation of NFAT and EGR-1 in the induction of the TF promoter, and a physical interaction between the two factors was indicated by co-immunoprecipitation assays. Another gene upregulated by VEGF predominantly via NFAT, which is not induced by EGF, is the DSCR-1 gene. The calcineurin inhibitor DSCR-1 seems to be induced by VEGF in a negative feed-back loop to limit NFAT activation. When we tested adenoviral overexpression of DSCR-1, VEGF-mediated induction of tissue factor mRNA was reduced, and complete suppression could be achieved by a combination of viruses expressing DSCR-1 and NAB2, a corepressor of EGR-1. These findings support that both, NFAT and EGR-1, are required for tissue factor upregulation in response to VEGF.
Keywords: EGR-1; NFAT; VEGF; endothelial cells; tissue factor; DSCR-1